Effect of metformin on the epigenetic age of peripheral blood in patients with diabetes mellitus - Li, Man; Bao, Litao; Zhu, Ping; Wang, Shuxia (Frontiers in Genetics, 2022)
Background: Metformin has been proved to have anti-aging effect. However, studies on how metformin affects global epigenetic regulation and its effect on the epigenetic clock in the diabetes mellitus (DM) patients is limited. This study aims to investigate the impact of metformin on the epigenetic age in subjects with type 2 DM. Results: We collected the peripheral blood of metformin group and the no metformin group of the 32 DM patients. Epigenetic clock was used to estimate the epigenetic age acceleration of the two groups. The results were presented as the following: 1) the metformin slow down the epigenetic age of the DM patients by an average of 2.77 years. 2) we observed a significant enrichment in the regulation of histone methyl-transferase activity (H3K9 specific) 3) we identified 144 differentially methylated positions (DMPs), the top 20 cytosine–guanine dinucleotides (CpGs) and their associate genes with the most consistent changes in the DNA methylation profile were selected: EPM2AIP1, MUC17, FNDC1, HLA-DOB, TRPC4, ESRRB, ADCY2. The major functions of most top-level differential methylation sites and the cellular signaling pathways they represent are related to aging process. Conclusions: Here we demonstrated that metformin could perform an anti-aging effect by slow down the epigenetic clock